Soluble Fc Receptor for IgM in Sera From Subsets of Patients With Chronic Lymphocytic Leukemia as Determined by a New Mouse Monoclonal Antibody - Mahmoudi Aliabadi, Pedram; Teuber, Ruth; Jani, Peter K.; Wilson, Landon; Enghard, Philipp; Barnes, Stephen; Chiorazzi, Nicholas; Radbruch, Andreas; Melchers, Fritz; Kubagawa, Hiromi (Frontiers in Immunology, 2022)
The Fc receptor for ancient IgM molecules (FcµR) is the newest member of the FcR family, is selectively expressed by lymphocytes, and is distinct from FcRs for switched Ig isotypes that are expressed by various immune cell types as well as non-hematopoietic cells. From studies of Fcmr-ablated mice, FcµR was shown to have a regulatory function in B cell tolerance, as evidenced by high serum titers of autoantibodies of the IgM and IgG isotypes in mutant mice. In our previous studies, both cell surface and serum FcµR levels were elevated in patients with chronic lymphocytic leukemia (CLL), where antigen-independent self-ligation of B cell receptor (BCR) is a hallmark of the neoplastic B cells. This was assessed by sandwich ELISA using two different ectodomain-specific monoclonal antibodies (mAbs). To determine whether the serum FcµR is derived from cleavage of its cell surface receptor (shedding) or its alternative splicing to skip the transmembrane exon (soluble), we focused on establishment of soluble FcµR (solFcµR)-specific assessment. Taking advantages of the unique nature of transductant stably producing His-tagged solFcµR and of an in vivo differential immunization, we made a new mouse IgG1κ mAb specific for human solFcµR that reacted with serum FcµR in subsets of CLL patients. This mAb will be used for verifying the hypothesis that the production of solFcµR is the consequence of chronic stimulation of BCR.